THE IMPORTANCE OF SMART LIGHTING AND SENSOR SYSTEMS FOR IMPROVING VEHICLE VISIBILITY (IN THE CONTEXT OF DARKNESS AND ADVERSE WEATHER CONDITIONS) - Qosimov, Abbosjon Sharofidin ogli (Educational Research in Universal Sciences, 2025)
This article analyzes innovative solutions aimed at improving the visibility of vehicles in dark conditions and adverse weather (fog, rain, snow). It highlights the effectiveness of smart lighting and sensor systems powered by Artificial Intelligence (AI), Infrared (IR) technologies, and the Internet of Things (IoT). These intelligent systems enhance vehicle visibility, increase safety, save energy, and provide real-time alerts to drivers. The article also discusses the integration of IoT and AI technologies into transportation systems, enabling vehicle condition monitoring and automatic decision-making. Such systems play a crucial role in preventing road accidents under poor weather conditions. The article calls for the expansion of advanced systems aimed at enhancing transportation safety and visibility through innovative technologies.